TINJAUAN YURIDIS PELAKSANAAN UNDANG-UNDANG NOMOR 22 TAHUN 2001 TENTANG MINYAK DAN GAS BUMI DI KOTA SAMARINDA (Studi Kasus Putusan Nomor 588/Pid.B/2014/PN SMR) - Priastama Adiyoga (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT This thesis aims to determine the extent to which the execution of criminal sanctions against misuse of the transport and / or commercial subsidized oil fuel and to determine the legal considerations of the judge in the case ruled on 588 / Pid.B / 2014 / PN SMR.This research was conducted in the District Court of Samarinda to do an interview to the parties of the agency is directly related to the issues to be discussed. The author also collecting data related to the object of study and a study of literature by way of examining the books, literature and legislation relating to the issues discussed in this thesis. The findings obtained from this study is the application of criminal law by the judge in a criminal case 588 / Pid.B / 2014 / PN SMR.Based on the results of the study, the authors considered was the fulfillment of the elements of a criminal offense under article 5 of Law 22 of 2001 on Oil and Gas. In this ruling the judge impose a criminal sanction against the defendant "Ilham Bin Muslims" form of imprisonment for six (6) months and a fine of Rp.3.000.000,00 (three million rupiah). This thesis aims to be useful as a source of public knowledge in understanding the definition of the crime of abuse of Subsidized Fuel haulage and know the elements of the offense in issue.The author expects completion of this thesis can be a useful contribution to society and appealed to the law enforcement agencies that the perpetrators of such offenses can be subject to strict sanctions according to the Law in force referred to in Article 55 of Law No. 22 of 2001 so as to minimize the occurrence of this criminal act. Keywords: subsidized fuel, Abuse, Event Transportation and Distribution of fuel.